ҚАРАҚАЛПАҚ ХАЛЫҚ ДӘСТАНЫ «ЕДИГЕ»ДЕ АЛҒЫС, ПӘТИЯ ҲӘМ ТИЛЕКЛЕРДИҢ ҚОЛЛАНЫЛЫЎ ӨЗГЕШЕЛИГИ - Абдимуратов, Л.А. (SCIENCE and SOCIETY, 2025)
The article gives data on gratitude, in the “Ediga” of the Karakalpak folk epic. Here, the features and forms of gratitude are analysed. In some episodes of the epic, the educational value of gratitude is mentioned.
Keywords: fundamental; material; form; episode; gratitude; blessing